45. THE EVALUATION OF THE RESULTS OF TOTAL HIP REPLACEMENT IN PATIENTS WITH ASEPTIC NECROSIS OF THE FEMORAL HEAD AT HA TINH TTH GENERAL HOSPITAL (2022-2023) (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluate the results of total hip replacement treatment in patients with aseptic necrosis of the femoral head treated at Ha Tinh TTH General Hospital (2022-2023).Method: The study was designed according to the uncontrolled intervention research method.Results: Among 180 patients undergoing total hip replacement surgery, the rate of moderate pain decreased from 78.9% after 1 month to 2.8% after 3 months and 6 months. Insignificant pain increased from 13.9% at 1 month after surgery to 97.2% after 3 months and 88.8% after 6 months. After 1 month, 93.3% of patients had to use a cane when walking, decreasing to 56.1% after 3 months and 5% after 6 months. The proportion of patients with joint range of motion from 161-210° increased from 0% after 1 month to 86.6% after 6 months. The average Haris score increased from 62.50 ± 5.82 after 1 month to 80.99 ± 6.39 after 3 months and 89.19 ± 5.93 after 6 months, the difference is statistically significant p < 0 ,01.Conclusion: Total hip replacement surgery for patients with aseptic degeneration of the femoral head has good treatment results, with few complications and complications.
Keywords: Femoral head, necrosis, hip replacement.